1996
DOI: 10.1111/j.1432-1033.1996.0566u.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Activates Transcription of the Heme Oxygenase Gene in Mouse M1 Cells Through Oxidative Activation of Nuclear Factor κB

Abstract: It has been known for a long time that heme oxygenase (HO) is a key enzyme in heme catabolism, and it was found to act as an oxidative-stress protein to produce carbon monoxide, which has similar actions to those of nitrogen monoxide. We examined transcriptional control of the HO gene in mouse M1 (myeloleukemia) cells during treatment with lipopolysaccharide (LPS; an oxidative reagent). Since the promoter region of this gene in human cells contains a 12-O-tetradecanoyl-phorbol-l3-acetate(TPA)-responsive elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 16 publications
2
41
2
Order By: Relevance
“…9). This result relates, in addition to the aforementioned role of ROS in modulation of HO-1 expression, to the observation that the HO-1 gene promoter bears a motif known as the heme-responsive element, to which NF-B binds upon cell treatment with oxidative reagents, such as H 2 O 2 (58). Furthermore, it must be emphasized that the binding of NF-B to a number of target genes in T cells has been proven to be redox-sensitive (66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). This result relates, in addition to the aforementioned role of ROS in modulation of HO-1 expression, to the observation that the HO-1 gene promoter bears a motif known as the heme-responsive element, to which NF-B binds upon cell treatment with oxidative reagents, such as H 2 O 2 (58). Furthermore, it must be emphasized that the binding of NF-B to a number of target genes in T cells has been proven to be redox-sensitive (66).…”
Section: Discussionmentioning
confidence: 99%
“…Also, an NF-B-binding motif has been found in the promoter of the mouse Ho-1 gene (58). In order to assess whether NF-B activation is essential for the induction of HO-1 expression by 15dPGJ 2 in human lymphocytes, the NF-B-blocking peptide SN50 was used.…”
Section: Dpgj 2 Induces Ho-1 Expression In Human Lymphocytesmentioning
confidence: 99%
“…To date, several studies have indicated that NF-κB can control the induced expression of HO-1 (23)(24)(25). The κB site in the HO-1 promoter, which is thought to control this induced expression, was first described by Lavrovsky and colleagues (23).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23]. The function of NF-κB in regulating HO-1 expression in human cells is controversial because more than one study suggests a direct relationship between NF-κB and HO-1 activity (24,25); however, other studies investigating the HO-1 promoter show that the κB response element is unresponsive to several HO-1 inducers (26). The present study was undertaken to further define the role of NF-κB and Nrf2 in regulating HO-1 gene expression in AML.…”
Section: Introductionmentioning
confidence: 99%
“…It is always possible that secondary effects of chemical treatments rather than their oxidantJantioxidant properties are responsible for the effects presented in Table 4. However, a number of studies have used oxidants to block the effects of antioxidant compounds (302,(306)(307)(308) and vice versa (21,290,293,294,(309)(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320)(321). Furthermore, structural analogs that lack antioxidant properties fail to induce these changes (322).…”
Section: Oxidative Stress and Gene Regulationmentioning
confidence: 99%